Lending Mary - White, Eliza Orne; Paull, Grace (Houghton Mifflin Company, 1934)
A nine-year-old girl, Mary is lent to a cousin while her mother takes a vacation. Mary is given a calendar and a black and red pencil and is instructed to cross off the days till her mother returns. A red pencil is for red-letter days when she's happy. Surprisingly Mary uses the red pencil constantly. Except for feeling lonely on foggy days, Mary experiences mostly happy times due to the arrival of a young cousin and a rather strange uncle.
Illustrated t.-p.
A nine-year-old girl, Mary is lent to a cousin while her mother takes a vacation. Mary is given a calendar and a black and red pencil and is instructed to cross off the days till her mother returns. A red pencil is for red-letter days when she's happy. Surprisingly Mary uses the red pencil constantly. Except for feeling lonely on foggy days, Mary experiences mostly happy times due to the arrival of a young cousin and a rather strange uncle.
Keywords: Uncles / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2010117320; Cousins / Juvenile fiction. / http://id.loc.gov/authorities/subjects/sh2009122222; Girls / Conduct of life / Juvenile fiction.